Peran Bimbingan Perkawinan Pranikah dalam Mencegah Pernikahan Dini: Studi Kasus Kantor Urusan Agama (KUA) Kecamatan Puring Kabupaten Kebumen - Arini Nur Akhsani; Muhammad Arifin Badri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the role of premarital counseling implemented by the KUA of Puring sub-district in reducing early marriage. Using a descriptive qualitative approach, this study examines the implementation of the